Contemporary economic problems, 1979 - Fellner, William (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1979)
The volume has resulted from the work of economists who have discussed their research with each other on several occasions during this year, as they have in previous years.The titles of the sections will rightly suggest to the reader that the studies have to do with difficulties that have developed in an inflationary era and with the relationship between the macro- and the microeconomic aspects of these, as well as with issues of economic policy that need to be faced in the effort to overcome the difficulties.
rpm 08/05/2017
Loans
Keywords: Inflation (Finance) -- United States; Monetary policy -- United States; Fiscal policy -- United States; United States -- Economic problems -- 1971-; United States